PEMBERDAYAAN PENDIDIKAN KARAKTER ISLAMI SISWA TPA DI DESA SINDANGMULYA - Nurfadilah; Isfandayani; Irham (Universitas Islam 45 Bekasi, 2025)
The development of Islamic character among children in Al-Qur’an Education Parks (TPA) remains a crucial challenge, particularly in optimizing character formation aligned with Islamic values. This community service project aims to strengthen the Islamic character of children at TPA Sindang Mulya Village through a structured mentoring program supported by additional educational approaches. The methods applied include mentoring activities combined with demonstration, cognitive, affective, and psychomotor strategies, all designed to foster holistic character development. The program was implemented for 30 days at TPA Sindang Mulya, with participants consisting of children actively enrolled in the TPA program. The findings indicate a significant improvement in children’s Islamic character, particularly in the aspects of honesty, politeness, and discipline. Mentoring proved to be effective in shaping attitudes and behaviors consistent with Islamic values while also enhancing the learning experience in both religious and social contexts. Furthermore, the structured combination of cognitive, affective, and psychomotor approaches allowed the children to internalize values more effectively and apply them in daily interactions. In conclusion, this community service demonstrates that mentoring programs can serve as an effective strategy for character building in TPA settings. Therefore, similar initiatives should be sustained and expanded to other communities to achieve broader impacts.